Association of dietary patterns with diabetes-related comorbidities varies among diabetes endotypes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zhu, Anna; Zaharia, Oana-Patricia; Strom, Alexander; Bönhof, Gidon J.; Goletzke, Janina; Trenkamp, Sandra; Wagner, Robert; et al. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Ernährung und Alltagsbewältigung - Ein Spannungsfeld für Individuum, Haushalt und Gesellschaft - Buyken, Anette; Libuda, Lars (DGEwissen)

Differentially Private Natural Language Models: Recent Advances and Future Directions - Hu, Lijie; Habernal, Ivan; Shen, Lei; Wang, Di (Findings of the Association for Computational Linguistics: EACL 2024, St. Julian’s, Malta, March 17-22, 2024)

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Modular 3D roller straightening – A new approach to straightening and forming of spring steel wires (X10CrNi18-8) - Dahms, Frederik Simon; Homberg, Werner (Materials Research Proceedings)
Abstract. Spring steel wires are usually supplied and stored on coils. The manufacturing and coiling processes of these wires induce inhomogeneous plastic deformations that lead to undesirable residual stresses and varying wire curvatures in the semi-finished product. These residual stresses and curvatures defects are causing varying process conditions in the subsequent manufacturing processes, which have a negative impact on the product quality, leading to wastage and thus affecting the economic and ecological efficiency. Especially the curvature deviations must be compensated for the stability of the subsequent processes. This is usually realised with roller straighteners, which are set manually by the machine operators only at the beginning of a process. In this paper, we introduce a new approach with a modular straightening-machine design and a new set-up process. The more isolated deformation behaviour in a module-based straightener overcomes the complexity of interactions between the close-positioned spaced straightening rollers. This is combined with a set-up process that is independent of conventional material testing, modelling the actual and batch-specific behaviour of the wire in the straightening process. The exact knowledge and time-consuming determination of the material properties thus becomes obsolete. The experimental investigations show the influence of defined straightening strategies on the residual stress evolution and the residual forming limit of the spring steel wires (X10CrNi18-8) in the new straightening process.

Experimentally Verified 22 kW, 30 kHz LLC Resonant Converter Design with new Control for a 1 MW Cascaded H-Bridge Converter - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (ECCE Europe 2024; IEEE Energy Conversion Congress & Exposition Europe)

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Protein intake and cancer: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Kühn, Tilman; Kalotai, Nicole; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose It has been proposed that a higher habitual protein intake may increase cancer risk, possibly via upregulated insulin-like growth factor signalling. Since a systematic evaluation of human studies on protein intake and cancer risk based on a standardised assessment of systematic reviews (SRs) is lacking, we carried out an umbrella review of SRs on protein intake in relation to risks of different types of cancer. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and cancer risk published before January 22th 2024, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Ten SRs were identified, of which eight included meta-analyses. Higher total protein intake was not associated with risks of breast, prostate, colorectal, ovarian, or pancreatic cancer incidence. The methodological quality of the included SRs ranged from critically low (kidney cancer), low (pancreatic, ovarian and prostate cancer) and moderate (breast and prostate cancer) to high (colorectal cancer). The outcome-specific certainty of the evidence underlying the reported findings on protein intake and cancer risk ranged from very low (pancreatic, ovarian and prostate cancer) to low (colorectal, ovarian, prostate, and breast cancer). Animal and plant protein intakes were not associated with cancer risks either at a low (breast and prostate cancer) or very low (pancreatic and prostate cancer) outcome-specific certainty of the evidence. Overall, the evidence for the lack of an association between protein intake and (i) colorectal cancer risk and (ii) breast cancer risk was rated as possible . By contrast, the evidence underlying the other reported results was rated as insufficient . Conclusion The present findings suggest that higher total protein intake may not be associated with the risk of colorectal and breast cancer, while conclusions on protein intake in relation to risks of other types of cancer are restricted due to insufficient evidence.

Dietary protein and blood pressure: an umbrella review of systematic reviews and evaluation of the evidence - Boeing, Heiner; Amini, Anna M.; Haardt, Julia; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Introduction This umbrella review aimed to investigate the evidence of an effect of dietary intake of total protein, animal and plant protein on blood pressure (BP), and hypertension (PROSPERO: CRD42018082395). Methods PubMed, Embase and Cochrane Database were systematically searched for systematic reviews (SRs) of prospective studies with or without meta-analysis published between 05/2007 and 10/2022. The methodological quality and outcome-specific certainty of evidence were assessed by the AMSTAR 2 and NutriGrade tools, followed by an assessment of the overall certainty of evidence. SRs investigating specific protein sources are described in this review, but not included in the assessment of the overall certainty of evidence. Results Sixteen SRs were considered eligible for the umbrella review. Ten of the SRs investigated total protein intake, six animal protein, six plant protein and four animal vs. plant protein. The majority of the SRs reported no associations or effects of total, animal and plant protein on BP (all “possible” evidence), whereby the uncertainty regarding the effects on BP was particularly high for plant protein. Two SRs addressing milk-derived protein showed a reduction in BP; in contrast, SRs investigating soy protein found no effect on BP. The outcome-specific certainty of evidence of the SRs was mostly rated as low. Discussion/conclusion This umbrella review showed uncertainties whether there are any effects on BP from the intake of total protein, or animal or plant proteins, specifically. Based on data from two SRs with milk protein, it cannot be excluded that certain types of protein could favourably influence BP.